2006
DOI: 10.1093/rpd/ncl030
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of annual effective dose from 238U and 226Ra due to consumption of foodstuffs by inhabitants of Tehran city, Iran

Abstract: The concentrations of (238)U and (226)Ra were determined in different foodstuffs purchased from markets in Tehran. Determinations of the radionuclides have been carried out using alpha spectrometry technique, on samples of egg, lentil, potato, rice, soya, spinach, tea and wheat. Average concentrations of natural radionuclides and foodstuff consumption rate were used to assess annual intake and based on intake values, the annual effective ingestion dose has been estimated for Tehran city residents. The measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…On the other hand, the activity obtained was compared with the data from other countries. As shown in the Table 3, the 120002-3 mean activity of all milk brands is similar to those reported from Brazil [23] but relatively higher than the data from Jordan [14], India [10], Saudi Arabia [12], Israel [24] and Iran [19] and considerably lower compared to the data from Nigeria [11] and Saudi Arabia [13). In respect to the activity of 40 K in the brands of milk under investigation, it shows a range of somewhat high values.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…On the other hand, the activity obtained was compared with the data from other countries. As shown in the Table 3, the 120002-3 mean activity of all milk brands is similar to those reported from Brazil [23] but relatively higher than the data from Jordan [14], India [10], Saudi Arabia [12], Israel [24] and Iran [19] and considerably lower compared to the data from Nigeria [11] and Saudi Arabia [13). In respect to the activity of 40 K in the brands of milk under investigation, it shows a range of somewhat high values.…”
Section: Resultssupporting
confidence: 71%
“…The obtained mean activity of radium-226 has been compared with the literature (Table 3). It shows that the mean activity of 226 Ra in powdered infant's milk available to Malaysian infant's population is higher than in Slovenia [18], Iran [19], Poland [20], India [10], Saudi Arabia [12] and Jordan [14] but significantly lower than the reported data from Nigeria [11] and Saudi Arabia [13]. With the regard to 232 Th (an indicator for 228 Ra) activity in the sampled milk brands, the activity ranged between 0.31±0.10 Bqkg -1 (Anmum) to 8.57±2.11 Bqkg -1 (SMA Gold) and an average value of 2.55±2.48 Bqkg -1 (all brands).…”
Section: Resultsmentioning
confidence: 95%
“…The annual effective dose from 228 Ra was higher due to the three plant-based food groups to the three consumer groups in India (Kudankulam). Hosseini et al (2006) have calculated the effective dose due to plant foods to the inhabitants of Tehran City, Iran and found that wheat contributed the highest and lentil (legumes) the lowest dose. This also implies that the higher consumption rate of cereals increases the annual dose rate in spite of low activity concentrations in them.…”
Section: Annual Intake and Annual Effective Dose From 228 Ra And 226 Ramentioning
confidence: 99%
“…Wheat flour, the "Staff of Life", has been an essential commodity to human existence through the centuries and is currently the most widely consumed staple food. Moreover, numerous studies were conducted worldwide to investigate natural radionuclides in food consumed in different parts of the world (Hosseini et al 2006;Jibiri & Okusanya 2008;Ababneh et al 2009;Desimoni et al 2009). For a systematic treatment, a methodical approach is undertaken that focuses on a wheat flour type of food per study.…”
Section: Introductionmentioning
confidence: 99%